The Effectiveness of Adding Probiotic to Antimicrobial Agents for the Treatment of Bacterial Vaginosis: A Systematic Review - Darmayanti, Aquartuti Tri; Murti, Bhisma; Susilawati, Tri Nugraha (Indonesian Journal of Medicine, 2017)
Background: Common antimicrobial regimens for treating bacterial vaginosis often cause recurrence and bacterial resistance. Previous studies have reported that a combination of antimicrobial and probiotic consisting of Lactobacillus spp. Is an effective treatment for recurrent bacterial vaginosis. Lactobacillus plays an important role in vaginal health by replacing the pathogenic colonies in vagina. This study aimed to determine the effectiveness of adding probiotic to antimicrobial therapeutic for the prevention of  bacterial vaginosis(BV) recurrence.Subjects and Method: A systematic review was conducted by searching the following databases: PubMed, Science Direct, Web of Science, Springer Link and the Cochrane. The review included randomized controlled trials (RCTs) conducted in primary hospitals and private clinics. The Amsel criteria and Nugent score were used for diagnosis appraisal of bacterial vaginosis. were included in this systematic review consisting of the two types of bacterial vaginosis treatment.  All pooled data analyses were based on random-effects models and intention to treat (ITT). Data were analyzed using Rev Man 5 software.Results: The review included 5 RCTs involving 692 women on reproductive age underwent treatment of BV for 5 days or more.The studies showed that combination of probiotic and antimicrobial treatment reduced the risk of bacterial vaginosis recurrence a half time compared to antimicrobial treatment alone(RR= 0.49; 95% CI= 0.17 to 1.44).Conclusion: Adding probiotic to antimicrobial regimens is more effective than antimicrobial regimens alone for treating bacterial vaginosis recurrence.Keywords: probiotic, antimicrobial, bacterial vaginosis recurrence, randomized controlled trialCorrespondence: Aquartuti Tri Darmayanti. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: tutiaquar@gmail.com. Mobile: +6281329380114.Indonesian Journal of Medicine (2017), 2(3): 161-168https://doi.org/10.26911/theijmed.2017.02.03.03